Performance appraisal dysfunctions a review and a suggestion - Halachmi, Arie (Philippine Journal of Public Administration, 1992)
This paper reviews the inherent inconsistencies of performance appraisal. It explains why its dual use of account for the past and to improve future performance can be paradoxical The paper describes -the concept of performance -targeting as a possible approach for productivity enhancement without some of the dysfunctions of performance appraisal.